Since N is normal bNb^-1 = N ==> aNbN = a(bNb^-1)(bN) =

**abN**(b^-1b)N = abN1N =**abN**.1 Answers · Science & Mathematics · 25/03/2014

Matlab is a standalone software for your computer. You can't use it on the internet. It is a high level programming language used to solve math problems. Although, you can use it for simpler things that a...

1 Answers · Science & Mathematics · 03/09/2007

Use this site for a final result: http://integrals.wolfram.com/index.jsp

1 Answers · Science & Mathematics · 21/05/2007

Simply consider the triangle

**ABN**. It is isosceles so AN = BN. We know this because...2 Answers · Science & Mathematics · 07/01/2011

✐Explanation✐ Recall that: y = abⁿ This formula is called Exponential Decay...

2 Answers · Science & Mathematics · 01/12/2009

Suppose G/N is Abelian. Then,

**abN**= (aN)(bN) = (bN)(aN) = baN So, N...1 Answers · Science & Mathematics · 02/04/2009

...2x^2) (4x) = 32 x cos (2x^2) d/dV [ ( (nRTsin(V)) / 2v ) +

**abn**^2] = [ nRT cos V (2V) - nRT sin V (2) / (2V...1 Answers · Science & Mathematics · 16/01/2010

I answered the first problem for you. 1. y = abⁿ Since "a jet ski depreciates at 11% of its original...

1 Answers · Science & Mathematics · 12/02/2011

...⁻¹b + nC2 aⁿ⁻²b² + ... + nC(n-1) abⁿ ⁻¹ + nCn bⁿ (a+b)ⁿ = Σ(i=0..n) nCi...

1 Answers · Science & Mathematics · 13/12/2009

... So... AD + BD + BP + NP = 32 ********** #2:

**ABN**is equilateral, which means each of its angles is...1 Answers · Science & Mathematics · 20/12/2007